The octagonal shape in Arab Islamic architecture - Hussein, Osama Mansour; Ali, Farooq Muhammad; Hashim, Basim Hasan (Al-Adab Journal, 2020)
The octagonal shape is characterized by the formalities of functional patterns, whether in Islamic architecture or the planning of Islamic cities as a pattern that was the beginning of the Islamic era. It is noted that the sides of the octagonal shape have the ability to space organization by achieving a series of successive architectural gradients that are consistent with the nature of the building and thus increased privacy The building and the city gained an architectural importance that made them different from the rest of the Islamic architecture.